Quantifying the Dispersion of Rainfall through the Box Whisker Technique - Rani, Seedari Ujwala; Kishore, Modem Ravi; Rani, N. Sri Vidya; Sunanda, N. (Science and Technology: Recent Updates and Future Prospects Vol. 12, 2024)
The whole study period of rainfall was divided into two sub-periods. The rainfall dispersion before and after the break year was analyzed through the Box Whisker technique to show the dispersion in quantity change in rainfall patterns in Microsoft Excel. Box whisker plots are non-parametric techniques which display variation in samples of a statistical population without making any assumptions about the underlying statistical distributions. This tool helps in comparing the quantity and dispersion of monthly and seasonal rainfall. It is a convenient way of graphically depicting groups of numerical data through their five number summaries, smallest observation (sample minimum), lower quartile (Q1), median (Q2), upper quartile (Q3) and largest observation (sample maximum). The spacing between the different parts of the box helps indicate the degree of dispersion (spread), and skewness in the data and identify outliers [1].